Determination of traditional food modification factor towards Terengganu’s keropok lekor / Malissasahila Abdul Manap - Abdul Manap, Malissasahila (2011)
Traditional food can be defined as a product with specific raw materials or food made from ancient or historic recipe with a specific process. In order to be traditional, a product must be linked to a country and it also must be part of a set of traditions, which will necessarily ensure its continuity. However, modification such as the application of new process, shape and ingredient has been applied to this traditional food. The modification on traditional food might affect the identity of the region and also to the food itself. Thus, this study comes out with three objectives; to determine the business operator perception on keropok lekor modification, to determine the element of keropok lekor modification’s factor based on business operators’ practices and to identify the most practices factor of food modification that effect towards the authenticity of keropok lekor. The researcher conduct the study at four districts in Terengganu area and the datawas gathered through a self-administered questionnaire. Several statistical tests namely Kruskal-Wallis test of homogeneity, frequency test, descriptive test by looking at mean scores and Spearman Rho to test the relationship between variable have been conducted to obtain the finding for this study. From the analyses, results showed the business operator positively perceived that the modification happen to Terengganu’s keropok lekor. The shortage of the ingredients and increasing price of the raw material lead them to modified keropok lekor and the ingredient is the most practices factor of modification. Furthermore, maintaining traditional food is very important because it value to the country. Every business operator, consumer and government must responsible to make sure these foods sustain with their image, identity and uniqueness. Therefore, future generation could benefit and know about this traditional food and until forever the keropok lekor will not lost and the heritage be prolonged.